Abdominal Obesity is a Risk Factor for Ischemic Stroke (Bangladesh Journal of Neuroscience, 2014)
We carried out case control study aimed to evaluate abdominal obesity as a risk factor for ischemic stroke. Though it became established as a risk factor for cardiovascular disease, still its association with stroke is less clear. We have taken ninety cases with ischemic stroke and compare waist to hip ratio & waist circumference with same numbers of age and sex matched stroke free people as controls. There are standard markers of abdominal obesity & their cut-off values and ways of measurement were taken from International Diabetic Federation. Both increase waist to hip ratio (63.3% in cases & 26.7% in controls) and increase waist circumference (66.7% in cases & 25.6% in controls) were significant (P1) in ischemic stroke patients. After adjusting the significant risk factors in all age and sex matched cases and controls by conditional logistic regression analysis, WHR and WC still showed significant strength of association with ischemic stroke in all groups. The increase abdominal obesity markers were found to have greater association in both female and male cases in relation to their control counterparts. So, in the light of current study we may suggest that abdominal obesity defined as increase waist circumference and waist to hip ratio attribute considerably to the estimate of ischemic stroke events. Bangladesh Journal of Neuroscience 2011; Vol. 27 (2) : 69-73 DOI: http://dx.doi.org/10.3329/bjn.v27i2.17545